The relationship between service marketing mix, service quality, service value and customer satisfaction in commercial car parking facilities - Ahmad Fiaza, Abdul Shukor (2016)
The role of car park facilities in economic activities, properties market and human life is imperative. The population growth and vehicle possession in tandem with the rapid development of building construction to support commercial activities in cities with scarcity of parking space, have been well identified and have become a major concern in Malaysia. This phenomenon has raised several issues that affect the satisfaction of the Malaysian public as users of car park facilities. One of the recommended solutions was to have excellent parking services but why the Malaysian public is still not satisfied with how car park facilities are being managed is a puzzle. Based on the problem statement, this study focused on the relationships between service marketing mix, service quality, service value, and customer satisfaction of commercial car parking facilities in Malaysia. The study’s research framework was supported by the Stimulus-Organism-Response theory. Three of the four main constructs namely service marketing mix, service quality and service value were conceptualised as second order construct and assessed via the reflective-formative approach. Customer satisfaction which acted as a dependent variable was measured reflectively through six multi items. All the items in the study’s variables were assessed using the 7-point Likert scale. Data was derived from 182 car park customers who subscribed to monthly season passes from selected private offices in the Klang Valley. The response rate of 23%, was analysed using the SPSS and the SmartPLS software. This study found that the priority of mix elements were varied through the non-parametric Friedman Test and all direct relationships between service marketing mix, service quality, service value and customer satisfaction were found significant through the PLS-SEM methodology. Four indirect effect hypotheses to examine the role of service quality and service value as mediators were accepted as partial mediation. The study findings were discussed thoroughly and concluded with a discussion on the implications, the limitation of the study and recommendations for future study.